Distribution of vitamin B12 R-binder in carcinomas of the digestive tract. Issue 3 (March 1988) - Kudo, H; Ohshio, G; Ogawa, K; Kim, Y C; Wakatsuki, Y; Nakashima, Y; Yamabe, H; Inada, M
Abstract : To evaluate whether the increase in serum transcobalamin I, seen in patients with carcinoma, is caused by synthesis of R-binder to tumour cells, the distribution of vitamin B12 R-binder in 125 malignant growths of the digestive tract was studied. Positive staining for R-binder with immunoperoxidase was observed in 85 (70%) carcinomas. Positive staining for R-binder was observed in all four cholangiocarcinomas studied, but was absent in nine hepatocellular carcinomas. These findings suggest that determination of R-binder in liver tumours may be of some value in differentiating hepatocellular carcinomas and cholangiocarcinoma, and that synthesis of R-binder by tumour cells causes an increase in serum transcobalamin I.